2008
DOI: 10.4103/0973-6131.36789
|View full text |Cite
|
Sign up to set email alerts
|

Influence of yoga on mood states, distress, quality of life and immune outcomes in early stage breast cancer patients undergoing surgery

Abstract: Context:Breast cancer patients awaiting surgery experience heightened distress that could affect postoperative outcomes.Aims:The aim of our study was to evaluate the effects of yoga intervention on mood states, treatment-related symptoms, quality of life and immune outcomes in breast cancer patients undergoing surgery.Settings and Design:Ninety-eight recently diagnosed stage II and III breast cancer patients were recruited for a randomized controlled trial comparing the effects of a yoga program with supportiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
41
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(43 citation statements)
references
References 58 publications
2
41
0
Order By: Relevance
“…In studies with sufficient information to compare, attrition was greater among yoga participants in two studies [37, 47], among control participants in three studies [38, 48-49, 51-52, 54-56], and approximately equal across groups in four studies [41-43, 58]. Two trials reported 100% completion [39, 57].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In studies with sufficient information to compare, attrition was greater among yoga participants in two studies [37, 47], among control participants in three studies [38, 48-49, 51-52, 54-56], and approximately equal across groups in four studies [41-43, 58]. Two trials reported 100% completion [39, 57].…”
Section: Resultsmentioning
confidence: 99%
“…Treatment-related side effects, including sleep, fatigue, pain, appetite loss, nausea and vomiting, sequelae-related distress, and toxicity, improved among yoga participants in several studies [39, 41, 48-49, 52, 54, 57]. One study documented better post-operative outcomes, including decreased drain retention, earlier suture removal, and shorter hospitalization, among yoga vs. control participants [51]. …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…After examination of the titles and the abstracts, 138 studies met the inclusion criteria - 28 single armed trials [Table 1][32333435363738394041424344454647484950515253545556575859] and 110 randomized and nonrandomized controlled trials: 18 from 1996 to 2008 [Table 2],[606162636465666768697071727374757677] 34 from 2009 to 2012 [Table 3],[78798081828384858687888990919293949596979899100101102103104105106107108109110111] and 58 from 2013 to 2016 [Table 4]. [112113114115116117118119…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the effect of yoga was reported on the telomere length, telomerase activity, T-cell subsets, signaling pathways of inflammatory transcription genes, cytokines, nuclear factor kappa B, and cAMP response element binding protein. [77131] In the vast majority of the studies, the yoga intervention was found to be beneficial and yielded positive effect on all the measures.…”
Section: Resultsmentioning
confidence: 99%